The rise in female employment and the role of tax incentives : an empirical analysis of the Swedish individual tax reform of 1971 - Håkan Selin (Center for Economic Studies and ifo Institute (CESifo), 2009)
Sweden reached the 2007 OECD average level of female labor force participation already in 1974. Before, but not after, 1971 the average tax rate facing the housewife was a function of the income of her husband. By exploiting a rich register based data source I utilize the exogenous variation provided by the individual tax reform to analyze the evolution of female employment in Sweden in the beginning of the 1970's. Simulations suggest that employment among married women would have been 10 percentage points lower in 1975 if the 1969 statutory income tax system still had been in place in 1975.
Keywords: J21; H24; 330; female labor supply; income tax reforms; Frauenerwerbstätigkeit; Arbeitsangebot; Einkommensteuer; Steuerreform; Schweden